Can Sodium Thiosulfate Act as a Reversal Agent for Calcium Hydroxylapatite Filler? Results of a Preclinical Study - Danysz W; Nowag B; Hengl T; Kreymerman P; Furne C; Madeuf E; Höennscheidt C; Mraz Robinson D (Dove Medical Press, 2020)
Wojciech Danysz,1 Bartosch Nowag,1 Thomas Hengl,1 Peter Kreymerman,2 Céline Furne,3 Elise Madeuf,4 Christoph Höennscheidt,1 Deanne Mraz Robinson5,6 1R&D, Merz Pharmaceuticals GmbH, Frankfurt am Main, Germany; 2Medical Affairs, Merz North America, Raleigh, NC, USA; 3NAMSA, Chasse sur Rhône, France; 4Preclinical Studies, Voxcan, Marcy L´Etoile, France; 5Modern Dermatology of Connecticut, Westport, CT, USA; 6Yale-New Haven Hospital, New Haven, CT, USACorrespondence: Wojciech DanyszMerz Pharmaceuticals GmbH, Eckenheimer Landstrasse 100, Frankfurt am Main 60318, GermanyEmail Wojciech.danysz@merz.deIntroduction: Calcium hydroxylapatite microspheres suspended in a gel carrier of sodium carboxymethylcellulose (CaHA; Radiesse®) has demonstrated safe and effective restoration of facial volume in clinical trials, as well as collagen biostimulation leading to skin quality improvement. The potential with CaHA, as with any filler, to produce overcorrection and subsequent complications has led to the search for a reversal agent. Sodium thiosulfate (STS) was proposed based on experience with it as a chelating agent to treat calciphylaxis. Previous pilot studies with small sample sizes have suggested its efficacy in the reduction of CaHA volume and nodule formation. The present study focuses on the verification of this effect using various readout methods in preclinical experiments.Methods: We use both in vitro (co-incubation of STS with CaHA) and in vivo (injections in farm pig) methods with readout techniques such as 3D camera analysis, micro-computed tomography ex vivo (μCT), computed tomography in vivo (CT), histopathology and scanning electron microscopy.Results: We did not obtain any indications of CaHA degradation by STS, either in vitro or in vivo. 3D-camera analysis also did not show any decreasing effect of STS on CaHA. However, histology, μCT ex vivo, and CT in vivo indicated a decrease of Radiesse amount/volume after STS treatment, which could be attributed to dispersion effect. It should be noted that necrosis and haemorrhages were observed after STS treatment.Discussion: Results suggest no indication of CaHA microspheres degradation with STS and that the STS mechanism of action on CaHA is consistent with a dispersion effect. Observed necrosis is a further obstacle in the use of STS.Keywords: calcium hydroxylapatite, sodium thiosulfate, dispersion effect, computed tomography, histology, 3D camera